2013
DOI: 10.1115/1.4023556
|View full text |Cite
|
Sign up to set email alerts
|

Positional Error Estimation in Serial Link Manipulator Under Joint Clearances and Backlash

Abstract: The serial link manipulators are most commonly used for industrial applications. The positional accuracy is an important specification for performance evaluation of a serial chain manipulator. The factors influencing the positional accuracy of serial link robotic manipulator includes joint clearances, and drive backlash. This paper presents method for evaluating the effect of joint error on positional accuracy of the robotic manipulator. Serial chain Two Revolute Joint (2R) planar manipulator is modeled to pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…By optimizing the design parameters of the mechanism, the transmission angle error decreases by 8.44% 。 An optimization procedure was then implemented to obtain the design parameters that ensured a minimum position error. In turn, Jawale and Thorat [452] utilized a serial chain two revolute joint planar manipulator to study the position error of the end effector in workspace, where the clearance influence was taken as a major factor. The authors showed that the maximum error in the end effector position could be effectively predicted when clearances were considered in the analysis.…”
Section: Optimization and Control Of Mechanisms With Clearance Jointsmentioning
confidence: 99%
“…By optimizing the design parameters of the mechanism, the transmission angle error decreases by 8.44% 。 An optimization procedure was then implemented to obtain the design parameters that ensured a minimum position error. In turn, Jawale and Thorat [452] utilized a serial chain two revolute joint planar manipulator to study the position error of the end effector in workspace, where the clearance influence was taken as a major factor. The authors showed that the maximum error in the end effector position could be effectively predicted when clearances were considered in the analysis.…”
Section: Optimization and Control Of Mechanisms With Clearance Jointsmentioning
confidence: 99%
“…A serial chain two-revolute joint planar manipulator was modelled. Under the influence of the joint clearance, a formulation was presented to analyse the positional accuracy of the end effector [17]. A spherical parallel manipulator with clearance and manufacturing error was analysed to determine the pose error of the platform in the presence of these imperfections [18].…”
Section: • Clearance In a Joint Is Inevitable And Worsens The System mentioning
confidence: 99%
“…The model of motion reliability should take the contribution of factors to position accuracy into account. Actually, factors related to position accuracy are various, such as clearance [17], friction [18], and wear [19]. Many of them are unobservable and uncontrollable and even have coupling relationship between each other, which makes it difficult to establish a model including all factors.…”
Section: Mathematical Problems In Engineeringmentioning
confidence: 99%
“…In summary, combining (17) with (2) and (4), the motion reliability models for point-to-point path planning and continuous trajectory tracking can be obtained, respectively. The motion reliability model for point-point path planning is expressed as…”
Section: Motion Reliability Models Of Path Planning Taskmentioning
confidence: 99%